Anti-NMDA receptor encephalitis presenting as new onset refractory status epilepticus in COVID-19. (October 2020) - Monti, Giulia; Giovannini, Giada; Marudi, Andrea; Bedin, Roberta; Melegari, Alessandra; Simone, Anna Maria; Santangelo, Mario; Pignatti, Alessandro; Bertellini, Elisabetta; Trenti, Tommaso; Meletti, Stefano
Highlights: Autoimmune encephalitis and status epilepticus in COVID-19 can be challenging. Immunotherapy could be useful for anti-NMDAr encephalitis and SARS-Cov-2 infection. Cytokines storm could play a role for NORSE presentation in NDMA-R encephalitis.